Enhanced expression of transglutaminase 2 in anterior polar cataracts and its induction by TGF-β in vitro. Issue 11 (1st November 2002) - Wan, X H; Lee, E H; Koh, H J; Song, J; Kim, E K; Kim, C Y; Lee, J B; Kim, S-Y; Yao, K; Lee, J H
Abstract : Background/aims: Transglutaminase activity has long been implicated in the cataract formation. However, the precise mechanism of how it is produced and involved in this process remains unclear. Here the authors sought to examine whether transglutaminase 2 (TGase 2) is expressed in lens epithelial cells from patients with anterior polar cataracts, to determine whether TGase 2 expression is induced by transforming growth factor (TGF-β) in cultured lens epithelial cells, and to determine whether TGase 2 participates in the crosslinking of fibronectin in lens epithelial cells in vitro. Methods: Lens epithelial cells from anterior polar cataracts, nuclear cataracts, and non-cataractous clear lenses were examined for the expression of TGase 2 using reverse transcription-polymerase chain reaction, western blot analysis, and immunohistochemical analysis. The modulation of extracellular TGase 2 activity by TGF-β was measured by the formation of fibronectin polymers and the incorporation of fluorescein cadaverine into extracellular matrix proteins. The effect of TGase 2 overexpression was analysed by immunofluorescence staining and western blot analysis of human lens epithelial (HLE) B-3 cells transiently transfected with TGase 2 gene. Results: The expression of TGase 2 mRNA and its protein was markedly enhanced in lens epithelial cells from patients with anterior polar cataracts. Treatment of HLE B-3 cells with TGF-β caused an increase in TGase 2 protein, its extracellular activity, and the crosslinking of fibronectin. Transient transfection of HLE B-3 cells with the TGase 2 gene led to the increased production of fibronectin monomers and polymers. Conclusions: This study shows that TGase 2 is overexpressed in lens epithelial cells from anterior polar cataracts and that TGF-β may be a causative factor in the induction of TGase 2. The enhanced expression of TGase 2 might cause the accumulation and crosslinking of the extracellular matrix proteins and might play a part in anterior polar cataract development.